2016
DOI: 10.1007/978-3-319-42059-2_3
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs and Inflammation in Colorectal Cancer

Abstract: Colorectal cancers (CRC) are known to be related to inflammatory conditions, and inflammatory bowel diseases increase the relative risk for developing CRC. The use of anti-inflammatory drugs prevents the development of colorectal cancer.Several molecular mediators are connecting the pathways that are involved in inflammatory conditions and in carcinogenesis. By the way these pathways are tightly interwoven, with the consequence that a deregulation at the level of any of these molecular mediators can affect the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 106 publications
0
20
0
Order By: Relevance
“…These non-coding RNAs are classified, based on their length, into small non-coding RNAs (<200 nucleotides), including miRNA, and long non-coding RNA (>200 nucleotides), including nuclear paraspeckle assembly transcript 1 ( 42 , 43 ). A number of non-coding RNAs have potential transcriptional, post-transcriptional and epigenetic regulatory functions, and are often dysregulated in many types of disease including cancer ( 44 47 ). miRNAs (18–25 nucleotides) are the most studied class of non-coding RNAs and post-transcriptionally regulate mRNA stability and translation ( 48 ).…”
Section: Role Of Mirnas In Cancermentioning
confidence: 99%
“…These non-coding RNAs are classified, based on their length, into small non-coding RNAs (<200 nucleotides), including miRNA, and long non-coding RNA (>200 nucleotides), including nuclear paraspeckle assembly transcript 1 ( 42 , 43 ). A number of non-coding RNAs have potential transcriptional, post-transcriptional and epigenetic regulatory functions, and are often dysregulated in many types of disease including cancer ( 44 47 ). miRNAs (18–25 nucleotides) are the most studied class of non-coding RNAs and post-transcriptionally regulate mRNA stability and translation ( 48 ).…”
Section: Role Of Mirnas In Cancermentioning
confidence: 99%
“…Based on this research (Bachmayr-Heyda et al, 2015), some circRNAs were detected and the results showed that hsa_circ_0020397 was highly expressed in CRC cells. Subsequently, abnormal miRNA expression was found to be related to the occurrence, development and prognosis of CRC (Josse and Bours, 2016;Yamamoto and Mori, 2016). Using common bioinformatic algorithms (miRanda and RNAhybrid 2.2), miR-138 was predicted to have multiple binding sites on hsa_circ_0020397.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, one single miRNA effect lots of genes together, suggesting that they have the ability to control complex signal pathways including CRI. Lots of reports investigated the role of miRNAs in CRI, but studies of miRNAs in CRI in EC are quite limited [ 23 , 24 ]. Our previous study found that miR-302b was a potential molecular marker and inhibited proliferation by inducing apoptosis and repressed invasion potentially by targeting ErbB4 in ESCC [ 7 ].…”
Section: Discussionmentioning
confidence: 99%